2017
DOI: 10.3390/ani7020008
|View full text |Cite
|
Sign up to set email alerts
|

Season, Transport Duration and Trailer Compartment Effects on Blood Stress Indicators in Pigs: Relationship to Environmental, Behavioral and Other Physiological Factors, and Pork Quality Traits

Abstract: Simple SummaryFactors, such as ambient conditions, travel duration and vehicle design/compartment location have an impact on the welfare of pigs during transport, carcass bruises and meat quality. Based on this, we aimed to assess the effects of these factors on blood creatine kinase, lactate and cortisol concentrations in 384 pigs and assess their relationships with trailer temperature, and pigs’ heart rate and gastrointestinal tract temperature, behavior, carcass damage scores and meat quality. Although incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
6
37
2
Order By: Relevance
“…In conditions requiring intense physical activity (as in transportation), several authors reported a high level of blood lactate in the pigs that were transported in the summer in potbelly type vehicles when compared to those transported in the winter, being 17.8 vs 16.3 mmol L -1 , respectively . On the other hand, in a later study by Sommavilla et al (2017), the authors found higher lactate levels in swine transported during the winter when compared to those transported during the summer, being 20.72 vs 16.53 mM. The high levels detected in this study are due to the effects produced by low temperatures and shorter trips.…”
Section: Lactate Dehydrogenasecontrasting
confidence: 57%
See 1 more Smart Citation
“…In conditions requiring intense physical activity (as in transportation), several authors reported a high level of blood lactate in the pigs that were transported in the summer in potbelly type vehicles when compared to those transported in the winter, being 17.8 vs 16.3 mmol L -1 , respectively . On the other hand, in a later study by Sommavilla et al (2017), the authors found higher lactate levels in swine transported during the winter when compared to those transported during the summer, being 20.72 vs 16.53 mM. The high levels detected in this study are due to the effects produced by low temperatures and shorter trips.…”
Section: Lactate Dehydrogenasecontrasting
confidence: 57%
“…Pig transport during the summer in potbelly vehicles may show elevations in the concentration of this enzyme with values of 4424 U/L (3324-5888) when compared to winter transport conditions 2734 U / L (2054-3639). This suggests that heat stress played a significant role, leading to an increase in muscular effort (SOMMAVILLA et al, 2017). On the other hand, Correa et al (2014) reported lower levels of this enzyme concentration in the summer than in the winter with 4605 and 6865 U/L, respectively.…”
Section: Creatine Phosphokinasementioning
confidence: 94%
“…These events challenge the thermoregulatory response of animals that are usually already stressed due to handling in unfamiliar environments. Several studies have described the negative effects of high temperatures during transport, such as the risk of dehydration, weight loss, changes in behavior, reduction in food consumption, or changes in blood indicators, both in piglets [9] as in barrows and gilts [10]. Piglets transported under conditions of low temperature show a significant decrease in food consumption both during transport and for some days later [11].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of smaller and longer-lasting temperature sensors, it is now feasible to record high-frequency time series for body temperatures [13] for extended periods, both on the farm [14] and during transport [15]. Sensors can be placed in different locations on or in the body to measure temperature without surgical intervention, such as the gastrointestinal tract [10], the vagina [16], and the ear canal adjacent to the tympanic membrane. Of these three locations, the ear canal is considered the most convenient since it is easier to fix the sensors and they are not easily removed by the animals [17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors would like to add that “Sébastien Goumon was supported by Grant No MZERO0716 from the Czech Ministry of Agriculture” in the Acknowledgement Section of their paper published in Animals [1]. …”
mentioning
confidence: 99%